Potential of Glycine max-Based Cream in Restoring Skin Structure Through PDGF and Collagen Modulation After UVB Exposure - Bayu Murdalin; Agung Putra; Eko Setiawan (Poltekkes Kemenkes Surabaya, 2025)
Premature aging is caused by excessive activity in the sun, causing oxidative stress and inflammatory reactions, which include changes in skin structure such as shortening and thickening of collagen fibers, damage to elastic fibers, and changes in the proportion of collagen types in the dermis. The purpose of this study was to determine the effect of administering soy extract cream (Glycine max (L.) Merr) on PDGF concentration and collagen density in BALB/c mice exposed to UVB rays. The experimental study used a Post Test Only Control Group Design with 30 BALB/c mice divided into five treatment groups: a group of healthy mice (K1), a negative group without exposure to UVB rays (K2), a positive group exposed to UVB rays and smeared with vitamin E cream (K3), and a treatment group with a dose of soy extract cream (KEKD) 10% (K4) and 20% (K5). Data analysis used the One Way Anova statistical test. The results of the study showed significant differences in the average PDGF levels in each group: (K1) 149.5±7.1 ng/mL, (K2) 40.4±4.4 ng/mL, (K3) 88.6±41.7 ng/mL, (K4) 323.2±86.1 ng/mL, and (K5) 330.2±34.3 ng/mL, with the One Way Anova test obtaining a p value = 0.001 (p<0.05). The average collagen density of group (K1) was 50.10±12.33%, (K2) 32.75±6.6%, (K3) 33.07±7.48%, (K4) 41.07±10.8%, and (K5) 41.9±13.4%, with One Way Anova test showing p=0.088 (p>0.05), which means there is no significant difference in collagen density between groups. Administration of soy extract cream (KEKD) affected PDGF levels, but did not show a significant difference in collagen density in BALB/c mice exposed to UVB light.